Transporte eletrônico e propriedades termodinâmicas de nanobiomoléculas - Bezerril, Leonardo Mafra (2009)
We use a tight-binding formulation to investigate the transmissivity and the currentvoltage (I_V) characteristics of sequences of double-strand DNA molecules. In order to reveal the relevance of the underlying correlations in the nucleotides distribution, we compare theresults for the genomic DNA sequence with those of arti_cial sequences (the long-range correlated Fibonacci and RudinShapiro one) and a random sequence, which is a kind of prototype of a short-range correlated system. The random sequence is presented here with the same _rst neighbors pair correlations of the human DNA sequence. We found that the long-range character of the correlations is important to the transmissivity spectra, although the I_V curves seem to be mostly inuenced by the short-range correlations. We also analyze in this work the electronic and thermal properties along an _-helix sequence obtained from an _3 peptide which has the uni-dimensional sequence (Leu-Glu-Thr- Leu-Ala-Lys-Ala)3. An ab initio quantum chemical calculation procedure is used to obtain the highest occupied molecular orbital (HOMO) as well as their charge transfer integrals, when the _-helix sequence forms two di_erent variants with (the so-called 5Q variant) and without (the 7Q variant) _brous assemblies that can be observed by transmission electron microscopy. The di_erence between the two structures is that the 5Q (7Q) structure have Ala ! Gln substitution at the 5th (7th) position, respectively. We estimate theoretically the density of states as well as the electronic transmission spectra for the peptides using a tight-binding Hamiltonian model together with the Dyson's equation. Besides, we solve the time dependent Schrodinger equation to compute the spread of an initially localized wave-packet. We also compute the localization length in the _nite _-helix segment and the quantum especi_c heat. Keeping in mind that _brous protein can be associated with diseases, the important di_erences observed in the present vi electronic transport studies encourage us to suggest this method as a molecular diagnostic tool